PEMBENTUKAN UNDANG-UNDANG NO. 3 TAHUN 2022 TENTANG IBU KOTA NEGARA BERDASARKAN UNDANG-UNDANG NO. 12 TAHUN 2011 TENTANG PEMBENTUKAN PERATURAN PERUNDANG- UNDANGAN: Establisment Of Law No. 3 Year 2022 On The National Capital Ased On Law No. 12 Year 2011 On The Establisment Of Laws And Regulations B - Daffa, Muhammad; Edwar, Ferry (AMICUS CURIAE, 2024)
Enactment Law No. 3 of 2022 the National Capital City has both positive-negative responses,primarily stemming from IKN Law formulation process, considered to relatively fast, notoptimizing principles openness and public participation. There are different arrangements in IKNLaw which included realm special regional government regulated Constitution 1945 and Law no.23 year 2014 concerning Regional Government. Research problem 1) Is process of establishingLaw No. 3 year 2022 in accordance with provisions of Law no. 12 year 2011?; and 2) Is contentof Law No. 3 year 2022 concerning State Capital in accordance with Law no. 12 year 2011?. Thiswriting uses normative research with statutory approach that’s descriptive analytical withsecondary data that’s analyzed qualitatively from results literature studies and conclusions usingdeductive method. Study found IKN Law formation process wasn’t optimal with principlesopenness and public participation regulated in Article 5 letter g and Article 96 of Law no. 12/2011at drafting and discussion stage as well as IKN Law didn’t fulfill content material as consequenceof hierarchy of laws and regulations Article 7 Law no. 12/2011. IKN Law need revisions inaccordance with hierarchy laws and regulations with pay attention to provisions Law no.12/2011.